ARTIFICIAL INTELLIGENCE IN DETECTING DIVORCE RISK THROUGH SOCIAL MEDIA DATA: ETHICAL ANALYSIS AND FIQH PERSPECTIVES - Harahap, Hasbiah Tunnaim (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
The advancement of Artificial Intelligence (AI) has created new opportunities for large-scale data analysis, including data derived from social media. One of its emerging applications is the use of AI to identify potential divorce risks through couples’ digital interaction patterns. This study aims to examine the role of AI in detecting divorce risks based on social media data, while also considering digital ethics and Islamic jurisprudence perspectives. The research employs a qualitative, multidisciplinary approach involving literature review, normative analysis, and Islamic legal studies. The findings suggest that AI can make a positive contribution to divorce prevention efforts and the formulation of social policies. Nevertheless, several ethical challenges must be addressed, including issues of privacy, potential data misuse, and violations of individual rights. From the standpoint of Islamic jurisprudence, the application of this technology must align with key principles of Sharia, such as the prohibition of tajassus (spying), the protection of honor and dignity (ḥifẓ al-‘irḍ), and the pursuit of public benefit (maṣlaḥah). Therefore, integrating AI into socio-religious issues requires a clear ethical and legal framework to ensure conformity with Islamic values and applicable legal norms.